Kaempferia parviflora Extract Exhibits Anti-cancer Activity against HeLa Cervical Cancer Cells - Potikanond, Saranyapin; Sookkhee, Siriwoot; Na Takuathung, Mingkwan; Mungkornasawakul, Pitchaya; Wikan, Nitwara; Smith, Duncan R.; Nimlamool, Wutigri (Frontiers in Pharmacology, 2017)
Kaempferia parviflora (KP) has been traditionally used as a folk remedy to treat several diseases including cancer, and several studies have reported cytotoxic activities of extracts of KP against a number of different cancer cell lines. However, many aspects of the molecular mechanism of action of KP remain unclear. In particular, the ability of KP to regulate cancer cell growth and survival signaling is still largely unexplored. The current study aimed to investigate the effects of KP on cell viability, cell migration, cell invasion, cell apoptosis, and on signaling pathways related to growth and survival of cervical cancer cells, HeLa. We discovered that KP reduced HeLa cell viability in a concentration-dependent manner. The potent cytotoxicity of KP against HeLa cells was associated with a dose-dependent induction of apoptotic cell death as determined by flow cytometry and observation of nuclear fragmentation. Moreover, KP-induced cell apoptosis was likely to be mediated through the intrinsic apoptosis pathway since caspase 9 and caspase 7, but not BID, were shown to be activated after KP exposure. Based on the observation that KP induced apoptosis in HeLa cell, we further investigated the effects of KP at non-cytotoxic concentrations on suppressing signal transduction pathways relevant to cell growth and survival. We found that KP suppressed the MAPK and PI3K/AKT signaling pathways in cells activated with EGF, as observed by a significant decrease in phosphorylation of ERK1/2, Elk1, PI3K, and AKT. The data suggest that KP interferes with the growth and survival of HeLa cells. Consistent with the inhibitory effect on EGF-stimulated signaling, KP potently suppressed the migration of HeLa cells. Concomitantly, KP was demonstrated to markedly inhibit HeLa cell invasion. The ability of KP in suppressing the migration and invasion of HeLa cells was associated with the suppression of matrix metalloproteinase-2 production. These data strongly suggest that KP may slow tumor progression and metastasis in patients with cervical cancer. Taken together, the present report provides accumulated evidence revealing the potent anti-cancer activities of Kaempferia parviflora against cervical cancer HeLa cells, and suggests its potential use as an alternative way for cervical cancer prevention and therapy.